Spatial and temporal variations in source, diagenesis, and fate of organic matter in sediments of the Netravati River, India - Fernandes, Dearlyn; Wu, Ying; Shirodkar, Prabhaker Vasant; Pradhan, Umesh Kumar; Zhu, Zhuo‐Yi; Zhang, Jing; Limbu, Samwel Mchele (Hydrological processes, 2019)
Organic matter (OM) such as organic nitrogen plays a substantial role in the global biogeochemical cycling of bio‐reactive components—amino acids (AA) in aquatic environments. Spatial and temporal variations in source, diagenesis, and fate of organic nitrogen such as AA in sediments of small tropical rivers and the role of oxbow/meandering loops under changing climatic conditions are poorly investigated. This study assessed the spatial and seasonal variations in OM composition, source, and diagenesis of a tropical small mountainous river—Netravati River, India, for 1 year. Water samples were determined for suspended particulate matter, and surface sediments were examined for bulk parameters, surface area (SA), and the L‐ and D‐enantiomers of AA. The L‐ and D‐enantiomers of AA displayed subtle seasonal variations in composition and depicted varying degrees of diagenesis. The concentration of D‐enantiomer of AA was high and showed substantial contributions from bacteria, terrestrial source, and in situ production. The D‐arginine was the most abundant D‐enantiomer of AA in the study area, possibly due to extracellular secretion by bacterial species and adsorption onto sediments, and thus, it was protected from degradation. Degradation index was more negative at the oxbow and meandering loop stations during the dry season suggesting that local geomorphologic settings steer the diagenesis of OM within the river. A negative relationship between gamma‐aminobutyric acid and organic carbon:surface area (OC:SA) ratio and a positive correlation between tyrosine and OC:SA ratio suggested accelerated loss of OM. Furthermore, the concentrations of most bulk parameters were higher in the lower reaches during monsoon and premonsoon seasons. Taken together, changes in seasons have an operational control in distinguishing the composition, source, and diagenesis of spatial OM distribution. Moreover, oxbows and river meandering loops influence the diagenetic processes in small tropical river systems.